Identification of Atuveciclib (BAY 1143572), the First Highly Selective, Clinical PTEFb/CDK9 Inhibitor for the Treatment of Cancer. (16th October 2017) - Lücking, Ulrich; Scholz, Arne; Lienau, Philip; Siemeister, Gerhard; Kosemund, Dirk; Bohlmann, Rolf; Briem, Hans; Terebesi, Ildiko; Meyer, Kirstin; Prelle, Katja; Denner, Karsten; Bömer, Ulf; et al.
Abstract: Selective inhibition of exclusively transcription‐regulating PTEFb/CDK9 is a promising new approach in cancer therapy. Starting from lead compound BAY‐958, lead optimization efforts strictly focusing on kinase selectivity, physicochemical and DMPK properties finally led to the identification of the orally available clinical candidate atuveciclib (BAY 1143572). Structurally characterized by an unusual benzyl sulfoximine group, BAY 1143572 exhibited the best overall profile in vitro and in vivo, including high efficacy and good tolerability in xenograft models in mice and rats. BAY 1143572 is the first potent and highly selective PTEFb/CDK9 inhibitor to enter clinical trials for the treatment of cancer. Abstract : The benzyl sulfoximine atuveciclib (BAY 1143572), a potent and highly selective oral PTEFb/CDK9 inhibitor, exhibited the most promising overall profile with respect to potency, selectivity, physicochemical properties, and in vivo PK as well as in vivo potency in animal models during lead optimization. BAY 1143572 is the first selective PTEFb/CDK9 inhibitor to enter clinical evaluation for the treatment of cancer.